TECHNOLOGY OF CREATIVE FORMATION STUDENTS 'PERSONALITIES IN EDUCATIONAL PROCESSES - N.I. Zelenkova (Academy of Cognitive and Natural Sciences, 2000)
The conditions of the educational process and the conditions of its organization form methods, which help to develop the Creative qualifies of a person a covered in the article.